(untitled) (Forseti. Law Review, 2026)
Standard form contracting is a mechanism that has served to reduce transaction costs in real estate transactions. However, this practice carries significant implications for consumer rights; consequently, the State sanctions the inclusion of unfair contract terms in real estate consumer contracts. This article analyzes the unfairness of including a penalty clause triggered by the termination of a contract due to a consumer’s breach of their contractual obligations.